The Legal Dimensions of the Promise to Sell a Building off the Map in Jordanian Law - Abu hilaleh, Ibrahim Mudhe; Al Tarawneh, Abdallah Imhammad Khalaf (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: The study aims to clarify the legal concept of the promise contract to sell the off-plan building in light of the real estate property law. Also, to identify the key safeguards that protect the rights of the buyer if the seller fails to implement their obligations. Methods: The study employs a descriptive-analytical approach, involving the examination and analysis of the legal provisions pertaining to off-plan building sales within Jordanian legislation. It assesses the adequacy of these provisions in addressing the challenges associated with this type of contract. Results: The study concludes that the current real estate property law in Jordan lacks comprehensive provisions for addressing promise contracts related to off-plan building sales. This gap particularly concerns the absence of effective measures to safeguard the rights of buyers in case of seller non-compliance or insolvency. Conclusion: The study recommends amending Jordanian real estate property law to facilitate the transfer of land rights and building ownership from the seller to the buyer as construction progresses. This should be contingent upon the buyer’s fulfillment of their obligations, along with provisions for effective implementation and financial security, potentially through a bank guarantee or a legally defined mechanism for seizing a portion of the construction value.